2020
DOI: 10.1038/s41598-020-68920-4
|View full text |Cite
|
Sign up to set email alerts
|

Selective solvent filters for non-aqueous phase liquid separation from water

Abstract: Injectable filters permeable to water but impermeable to non-polar solvents were developed to contain non-aqueous phase liquids (NAPL) in contaminated aquifers, hence protecting downstream receptors during NAPL remediation. Filters were produced by injecting aqueous solutions of 0.01% chitosan, hydroxyethylcellulose and quaternized hydroxyethylcellulose into sand columns, followed by rinsing with water. Polymer sorption onto silica was verified using a quartz-crystal microbalance with dissipation monitoring. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 75 publications
0
7
0
Order By: Relevance
“…However, the stearic acid‐treated materials cannot be applied in the separation of oil‐in‐water emulsions due to the as‐prepared superhydrophobic filter paper can be changed into hydrophilicity by adjusting the drying temperature (200°C) 58 . In actual separation applications, the separation performance of filter paper will be different for organic solutions with different polarities 81 . The density and weight of organic solvent droplets can certainly affect the contact area.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the stearic acid‐treated materials cannot be applied in the separation of oil‐in‐water emulsions due to the as‐prepared superhydrophobic filter paper can be changed into hydrophilicity by adjusting the drying temperature (200°C) 58 . In actual separation applications, the separation performance of filter paper will be different for organic solutions with different polarities 81 . The density and weight of organic solvent droplets can certainly affect the contact area.…”
Section: Resultsmentioning
confidence: 99%
“…The density and weight of organic solvent droplets can certainly affect the contact area. Meanwhile, the affinity between stearic acid coating and organic solvent, likely explaining why some oil‐in‐water emulsions could flow through stearic acid coated filter papers such as trichloromethane and petroleum ether 81 …”
Section: Resultsmentioning
confidence: 99%
“…11). www.nature.com/scientificreports/ Our previous studies showed that injectable filters could retain hydrophobic solvents such as toluene and hexane 51 , and that HEC + injectable filters retained diesel droplets emulsified by bacterial biosurfactants 81 . Here, HEC + injectable filters retain toluene containing Cu 2+ ions, as shown by ICP-OES analyses (Table 9).…”
Section: Flow Test Experiments (Injectable Filters)mentioning
confidence: 99%
“…We use Nile red as the hydrophobic dye and tetrahydrofuran (THF) as organic solvent. The hydrophobic property of Nile red has previously been utilized for selective staining and detection of lipid droplets 13 , for protein characterization 14 , and to measure the effectiveness of injectable aqueous filters for subsurface separation of non-aqueous phase liquids 15 . Finally, ultraviolet-visible (UV–Vis) spetrophotometry is subsequently used to measure the dye concentration in the THF solution, which in turn is proportional to the residual oil volume.…”
Section: Introductionmentioning
confidence: 99%